Atividade neuroprotetora da fração tanino isolada da miracrodruon urundeuva e da catequina em modelos de morte celular induzida pela 6 - hidroxidopamina (6 - OHDA) em cultura de células mesencefálicas de rato - Nobre Júnior, Hélio Vitoriano (2003)
n the present work we showed the neuroprotective effects of catequin and tannin fraction (TF) on rat primary mesencephalic cells culture exposed to 6-hydroxidopamine (6-OHDA). TF was isolated from the stem bark of Myracrodruoun urundeuva, Brazilian medicinal plant, largely used as a female genital tract antiinflammatory. Cells exposed to 6-OHDA (200 p.M) showed 53% reduction on cellular viability and an increase of 53% on lipidic peroxidation and 4400% on nitrite levels as observed by MTT, TEARS and nitrite assays, respectevely. Results showed that catequin (100 |j.g/mL) induced a significant reduction on cell death caused by 6-OHDA on neuroprevention and neurorescue models. Catequin did not interfered with the increased levels of nitrite induced by 6- OHDA. However, catequin inhibited significantly lipid peroxidation on both models. Theses results sugest that neuroprotective action is related to antioxidant action of this polyphenol class. TF (10 e 100 ^ig/mL) significantly reverted neuronal death induced by 6-OHDA (neuroprevention model). However, on neuroprevention model it reverted cell death only in concentrations of 100 p.g/mL. TF also reverted lipid peroxidation induced by 6-OHDA on both models. Conversely, it did not reduced nitrite levels produced by 6-OHDA. The neuroprotective mechanism ofTF is probably related with mithocondrial protection and antioxidant activity presented by tannins from M. urundeuva wich may have clinical importance on neurodegenerative disorders as Parkinson's disease.